Snow depth and snow-base backscatter intensity from AWI extquotesingles airborne UWBM quad-polarized radar over Atka Bay (December 2022; ANTSI Project) - Steven Franke; Veit Helm; Oceane Hames; Christian Haas (PANGAEA, 2025)
This dataset contains snow depth and snow-base backscatter intensity for four polarizations (HH, VH, VV, HV) derived from airborne radar data acquired using the quad-polarized AWI ultra-wideband microwave radar (UWBM) during the Antarctic season of 2022/23 (December 5th, 2022). The profiles extend across Atka Bay extquotesingles snow-covered landfast sea ice in western Dronning Maud Land, East Antarctica. UWBM data was acquired to study snow drifts around icebergs and their radar signatures with a quad-polarized high-resolution radar system. The snow depth is defined as the snow between the snow-ice interface or the snow-flooded snow (slush or brine-wetted snow) interface.